Machinability and surface integrity investigation of Ni-based aerospace superalloys based on energy thresholds investigation and innovative pendulum-based machining - Xu, Dong-dong (2019)
Ni-based superalloys have been extensively used in high-value-added industries due to their excellent performance in extremely harsh environment, i.e. high strength at elevated temperature over the service life. However, their physical material properties also cause this class of materials difficult to be machined and yield to low surface integrity. Thus, the surface integrity related machinability evaluation of such kinds of superalloy is essential for safety critical components manufacturers (e.g. aerospace, nuclear, and marine) to increase their service life. However, the traditional evaluation methods are either time or money consuming as varieties of cutting experiments are needed to collect enough information. In addition, these methods could only assess a specific set of cutting parameters at a time. Therefore, with the varying combinations of cutting parameters, the test becomes complicated due to the fact that multiple factors need to be considered to establish the threshold of cutting parameters which ensure the compliance with required workpiece surface integrity. In particular, surface integrity related machinability is usually studied by conducting cutting tests on conventional machine tools by varying the cutting parameters and followed by part sectioning to analyse superficial layer damages, which is obviously time consuming and resourceful. The research project in this thesis is related to Rolls Royce plc. and SECO Tools AB, aiming to develop a novel method that is able to evaluate the surface integrity related machinability of materials quickly with a limited volume of workpiece. A Pendulum-Based Cutting Test (PBCT) methodology is proposed which allows quick cutting tests for surface integrity evaluation along with providing cutting energies associated with particular levels of workpiece surface damage; this is supported by an unified cutting energy model that links level of machined surface with energy partition in the cutting areas. This method could rapidly define the energy consumed during the cutting process that result in particular magnitudes of surface damage without using conventional machine tools, while with the ability to monitor the cutting process in detail with only limited amount of materials required. The test results show that the level of surface damage could be related by the input energy, while given different cutting parameters that yield the same input energy, then result in the same level of surface damage. This gives the possibility to define energy thresholds for ensuring that particular levels of surface damage are not exceeded; hence, there is no need to test various cutting parameters. Therefore, this approach introduces an advantage for optimization and selection of cutting parameters for specific surface integrity by studying the input energy levels of the cutting process rather than performing extensive machining trails with various cutting parameter combinations blindly. Moreover, this research proposes an innovative concept which is able to generate machined surface that covers a wide range of cutting speeds continuously on a very limited geometry sample through a single test, thus to allow to continuously study the cutting performance transition of materials (e.g. Ni-based superalloy) at different cutting conditions. An obvious chip morphology variation, i.e. serrated chips at the start areas and smooth chips at the end of the chip, can be achieved, due to the decrease of cutting speed during cutting process. Coupled with energy-based surface integrity evaluation method, the consumed energy in different cutting areas (shear, friction and ploughing) at different cutting speeds could be evaluated and correlated with the continuous cutting mechanism transition along with various cutting conditions. To quantitatively study the plastic deformation of acquired machined surface, Electron Back Scattering Diffraction (EBSD) techniques has been employed. The experimental results showed that this research introduces an efficient way to carry out the surface integrity investigation of materials. To conclude, a quick and simple method to evaluate the surface related machinability of materials in limited volume is of great interest for both academic and industrial areas. Therefore, as described above, the motivation of this thesis is to develop a new method to accomplish the anticipated ability. The innovative PBCT method supported by built energy evaluation model has been proposed to carry out the surface integrity related machinability evaluation tests for materials, while a quantitative method for surface damage level on machined components has been introduced to accurately identify the surface integrity. All of the demonstrations for the proposed concept and method are presented with Inconel 718 as examples, while detailed validation tests are discussed in this thesis.